2017
DOI: 10.5114/ceh.2017.71483
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hepatocellular carcinoma recurrence rate after postoperative direct-acting antivirals treatment – preliminary report

Abstract: Aim of the studyNew interferon-free direct-acting antiviral (DAA) therapy has led to major progress in hepatitis C virus (HCV) treatment. Current outcomes are promising, especially in compensated cirrhosis. However, there are reports of accelerated hepatocellular carcinoma (HCC) recurrence after surgery in patients treated with DAAs. The influence of DAA therapy on the timing and frequency of recurrence after surgical treatment needs further observation.Material and methodsFifty-one HCV infected patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
(29 reference statements)
1
13
0
2
Order By: Relevance
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…There are several issues relevant to DAA therapy among patients with HCC. First, initial data suggested a potential increased risk of HCC recurrence, [8][9][10][11][12][13][14] although subsequent studies did not support these findings. [15][16][17][18][19][20][21][22] Second, in response to the controversy around HCC recurrence risk, the timing of DAA therapy in relation to HCC management became a point of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Since these early studies, many cohort studies have been conducted to analyze this issue ( Table 1 ). Of the 14 published studies available as of 1 June 2018, four concluded that there was an increased risk of HCC recurrence after DAA treatment [ 60 , 77 , 80 , 81 ] while the other 10 did not conclude in an increased risk, the recurrence rate being compared or not to a control group according to the study design [ 79 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Beneficial Effects Of Hcv Treatmentmentioning
confidence: 99%
“…Several systematic reviews and metaanalyses have shown that IFN-free DAA therapy does not affect HCC recurrence (10)(11)(12)(13). In contrast, single-center studies have shown that IFN-free DAA therapy may have either promotive or suppressive effects on HCC recurrence (14)(15)(16)(17)(18). Thus, the studies reported to date present conflicting data.…”
Section: Introductionmentioning
confidence: 99%